STUDI LITERATUR: PARTISIPASI MASYARAKAT DALAM PENGELOLAANNDANA KELURAHAN BAGI PEMBANGUNAN PADA KELURAHAN BAGAN BESAR TIMUR - Muhammad Surya Fadillah; Deajeng Rima Anggraini; Sri Asdianty; Erinaldi (Jurnal Riset Multidisiplin Edukasi, 2025)
Village Fund Allocation (AAK) is a financial resource derived from the Regional Revenue and Expenditure Budget (APBD) allocated to urban villages to support development and community empowerment programs. This fund serves as a strategic instrument for planning and implementing development initiatives aimed at providing tangible benefits to local residents. This study aims to analyze the level of community participation in the management of village funds in Bagan Besar Timur Urban Village, particularly in the stages of planning, implementation, as well as monitoring and evaluation of development programs. The research employs a qualitative method with a descriptive approach. The findings indicate that community participation is reflected in active involvement in development planning deliberations, support during program implementation, and supervision of fund utilization to ensure transparency, accountability, and proper targeting. Community participation plays a crucial role in achieving effective and sustainable development. This study highlights the importance of strong synergy between the village government and the community in managing village funds for the collective benefit.